A 6-Month Follow-Up Study on Worry and Its Impact on Well-Being During the First Wave of COVID-19 Pandemic in an Italian Sample - Ongaro, Giulia; Cincidda, Clizia; Sebri, Valeria; Savioni, Lucrezia; Triberti, Stefano; Ferrucci, Roberta; Poletti, Barbara; Dell’Osso, Bernardo; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
The Italian state adopted serious safety measures to manage the COVID-19 pandemic in the year 2020. The lockdown was associated with negative psychological consequences in healthy populations, mostly in terms of anxiety, distress, depression, and even traumatic symptoms. This longitudinal study aimed at briefly documenting the psychological impact among an Italian sample, in terms of worry and its impact on psychological well-being levels, of the first wave of COVID-19, taking into account the changes in the lockdown scenario. A three-time follow-up survey was administered to 177 subjects (Female: 78%, Mage = 36.33), during (T0), at the end (T1), and 3 months after the end of the first lockdown (T2). Since the first wave of COVID-19, results showed a decrease in worry and the perception of virus diffusion’s controllability over time while psychological well-being increased. Furthermore, factors such as personality traits (neuroticism and agreeableness) and dysfunctional coping strategies predicted increases in worry levels at the end of the lockdown and 3 months after in the Italian context. However, worry levels during and at the end of the lockdown did not predict well-being levels 3 months after the end of the lockdown. Based on these findings, mental health policymakers should design tailored interventions able to improve the perception of virus diffusion management, as well as address the psychological needs of Italian citizens and support it, including a plan for the follow-up evaluation.